Using the TOPSIS method to select the best low-toxicity organic cosolvent for rice-based toxicity tests - Xingren Pan; Yi Kang; Jun-Feng Lu; Xiao-Zhang Yu (Ecotoxicology and Environmental Safety)
The application of low-toxicity cosolvents in phytotoxicity tests is a common technique to enhance the distribution of non-water-soluble organic pollutants in the aqueous phase. In this study, the physiological and biochemical responses of rice seedlings to four commonly used organic solvents i.e., dimethyl sulfoxide (DMSO), N,N-dimethylformamide (DMF), pyridine, and Tween-80 were investigated using 16 parameters to assess their impacts on rice plants. Results from phytotoxicity tests indicated that these organic solvents caused varying toxic responses in rice plants and significantly affected the uptake and distribution of mineral nutrients within rice tissues. In order to select the best organic solvent for rice-based toxicity tests among the four solvents with optimal concentrations, the technique for order preference by similarity to ideal solution (TOPSIS) was employed to minimize the variations across different treatment groups. Three different weighting coefficients, namely entropy weight coefficients (EWCs), contribution factor coefficients (CFCs), and combination effective coefficients (CECs) were adopted to calibrate the initially created evaluation matrices. All estimations were judged by the relative closeness coefficients, in which the higher relative closeness value means the better solution to the optimal result. Among the four organic solvents evaluated by TOPSIS, pyridine at 1.24 mmol/L emerged as the most effective solution for rice-based phytotoxicity tests. Overall, this study represents the first attempt to comprehensively evaluate the toxic responses of cosolvents to rice plants using the TOPSIS method. It also offers valuable insights into a number of ecotoxicological applications like the analysis of solvent-generated extracts of environmental matrices from soils and sediments, or the detection of organic compounds induced toxicity with cosolvents.